2000
DOI: 10.1007/bf03162387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidation of cobalt-based nanowires on NMR spin-lattice relaxation

Abstract: Nuclear spin-lattice relaxation measurements were performed on Co-based magnetic nanowires, in zero field and in 1 T applied field. A measurement method is developped that allows a confident interpretation of the experimental data. An enhanced relaxation due to a thermally activated phenomenon associated to oxidation is reported for the first time in the nuclear magnetic resonance of ferromagnetic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Others have addressed nanowires made of pure cobalt as well as Co-Cu alloys and multilayers. [35][36][37][38] In combination with X-ray diffraction (XRD) measurements, they studied the crystalline structure of those three kinds of samples for different synthesis parameters. They found that a fast deposition rate favors the appearance of a face-centered cubic (fcc) crystalline structure, while a pure hexagonal close packed (hcp) phase is formed using slow deposition rates.…”
Section: Introductionmentioning
confidence: 99%
“…Others have addressed nanowires made of pure cobalt as well as Co-Cu alloys and multilayers. [35][36][37][38] In combination with X-ray diffraction (XRD) measurements, they studied the crystalline structure of those three kinds of samples for different synthesis parameters. They found that a fast deposition rate favors the appearance of a face-centered cubic (fcc) crystalline structure, while a pure hexagonal close packed (hcp) phase is formed using slow deposition rates.…”
Section: Introductionmentioning
confidence: 99%